Effectiveness of Strength Training and Cardio on Body Fat Reduction - Erra Fazira; Hijrah Maulidiah Afifah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Increasing public awareness of healthy lifestyles has encouraged more people to engage in physical activity, particularly exercise programs aimed at reducing body fat. However, there is still debate regarding which type of exercise is more effective for improving body composition. This study aimed to analyze and compare the effectiveness of strength training and cardio training on body fat reduction among members of Bodyhaus Gym in Semarang. This research employed a quantitative experimental approach using a pre-experimental one-group pretest–posttest design. The sample consisted of 30 gym members who were participating in a weight-loss program. Data were collected through body composition measurements using a Body Composition Analyzer, including body fat percentage, body weight, Body Mass Index (BMI), and muscle mass before and after a one-month training program conducted four times per week. The data were analyzed using the Shapiro–Wilk normality test followed by nonparametric tests, including the Wilcoxon Signed Rank Test and Mann–Whitney U Test. The results showed that both strength training and cardio training significantly affected body fat reduction. Cardio training was more effective in reducing body weight, BMI, and body fat percentage, whereas strength training was more effective in increasing muscle mass. In conclusion, both training methods contribute to improving body composition, but each provides different physiological adaptations depending on the training objectives